Pelatihan Pembuatan Website Untuk Siswa dan Guru di SMA Muhammadiyah Program Khusus Kottabarat Surakarta - Ita Permatahati; Nutfah Ailul Ulun; Renata Fina Antika Cahyani (Universitas Kristen Indonesia Toraja, 2024)
As time goes by, information technology becomes more advanced and makes the public aware of technology, especially educational staff who must continue to impart their knowledge to students. With advances in website technology and the increasing number of fields that use websites, indirectly interest in creating websites has also increased. Blogs are one of the technological developments in the internet sector. Blog or weblog is a term used to describe a development of a personal website that makes it easier for users to display personal information on the Internet in an easy way. However, not all students and teachers at the Muhammadiyah Program Khusus Kottabarat High School of Surakarta understand creating personal websites, due to a lack of knowledge regarding creating a website, where by having a personal website for students and/or teachers, apart from being able to carry out personal branding, students and Teachers at Muhammadiyah Program Khusus Kottabarat High School of Surakarta can provide all forms of information that is useful for the school or even for each individual, by providing training to teachers and students is one way to increase knowledge and abilities in creating a website. And from this activity, the participants were able to build a website with the WordPress platform.